Glucan, water dikinase activity stimulates breakdown of starch granules by plastidial β-amylases - Christoph, Edner; Jing, Li; Tanja, Albrecht; Sebastian, Mahlow; Mahdi, Hejazi; Hasnain, Hussain; Fatma, Kaplan; Charles, Guy; Steven M., Smith; Martin, Steup; Gerhard, Ritte (American Society of Plant Biologists, 2007)
Glucan phosphorylating enzymes are required for normal mobilization of starch in leaves of Arabidopsis (Arabidopsis thaliana) and potato (Solanum tuberosum), but mechanisms underlying this dependency are unknown. Using two different activity assays, we aimed to identify starch degrading enzymes from Arabidopsis, whose activity is affected by glucan phosphorylation. Breakdown of granular starch by a protein fraction purified from leaf extracts increased approximately 2-fold if the granules were simultaneously phosphorylated by recombinant potato glucan, water dikinase (GWD). Using matrix-assisted laser-desorption ionization mass spectrometry several putative starch-related enzymes were identified in this fraction, among them b-AMYLASE1 (BAM1; At3g23920) and ISOAMYLASE3 (ISA3; At4g09020). Experiments using purified recombinant enzymes showed that BAM1 activity with granules similarly increased under conditions of simultaneous starch phosphorylation. Purified recombinant potato ISA3 (StISA3) did not attack the granular starch significantly with or without glucan phosphorylation. However, starch breakdown by a mixture of BAM1 and StISA3 was 2 times higher than that by BAM1 alone and was further enhanced in the presence of GWD and ATP. Similar to BAM1, maltose release from granular starch by purified recombinant BAM3 (At4g17090), another plastid-localized b-amylase isoform, increased 2- to 3-fold if the granules were simultaneously phosphorylated by GWD. BAM activity in turn strongly stimulated the GWD-catalyzed phosphorylation. The interdependence between the activities of GWD and BAMs offers an explanation for the severe starch excess phenotype of GWD-deficient mutants.